Hydrogen-selective natural mordenite in a membrane reactor for ethane dehydrogenation - Avila, Adolfo María (2014)
Lab-scale ethane dehydrogenation experiments with natural mordenite disks in a membrane reactor showed an increase in ethane conversion and ethylene yield compared to their equilibrium values. Experiments performed with larger membrane permeation area confirmed the trend that higher conversions are expected as the ratio of product permeation and product formation rates increases. Using the lab-scale membrane reactor module an ethylene yield enhancement of ∼17% was observed at 500 °C. At a higher reaction temperature (550 °C), ethane dehydrogenation experiments resulted in a ∼10% ethylene yield enhancement versus ∼6% for comparative experiments at 500 °C. At 550 °C the membrane reactor effectiveness improved since the H2 permeation rate increased proportionally more than its formation rate. This material screening test revealed natural mordenite as a material to be considered in the development of highly-integrated membrane reactor modules for dehydrogenation of alkanes.